2007
DOI: 10.1051/parasite/2007144299
|View full text |Cite
|
Sign up to set email alerts
|

Fox faeces and vole distribution on a local range: ecological data in a parasitological perspective forEchinococcus multilocularis

Abstract: Summary :The completion of the life cycle of Echinococcus multilocularis needs a spatial overlap between intermediate host species (voles) and definitive host (fox) faeces. Factors influencing the importance of this overlap were investigated in north eastern France. Kilometric transects were walked to collect fox faeces and to estimate vole relative densities through surface indices. Habitat and climatic conditions were the strongest predictors of the number of faeces collected, while vole densities had no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Instead, it can be hypothesised that the high infection level was the result of a sustainable high fox population density. Indeed, the fox density estimated using distance-sampling method varied between 3 and 4 individuals/km 2 (Guislain et al, 2007), which were the highest values recorded with the same protocol among 12 sites in northeast France (Ruette et al, 2003). Additionally, Reperant et al (2009) showed in the city of Geneva, that in the part where sarcoptic mange was present (and accordingly lower fox density) the E. multilocularis prevalence in A. scherman was significantly lower.…”
Section: Definitive Host Population Density and E Multilocularis Tramentioning
confidence: 92%
See 4 more Smart Citations
“…Instead, it can be hypothesised that the high infection level was the result of a sustainable high fox population density. Indeed, the fox density estimated using distance-sampling method varied between 3 and 4 individuals/km 2 (Guislain et al, 2007), which were the highest values recorded with the same protocol among 12 sites in northeast France (Ruette et al, 2003). Additionally, Reperant et al (2009) showed in the city of Geneva, that in the part where sarcoptic mange was present (and accordingly lower fox density) the E. multilocularis prevalence in A. scherman was significantly lower.…”
Section: Definitive Host Population Density and E Multilocularis Tramentioning
confidence: 92%
“…There, medium-height vegetation edges and road banks were habitats where the density of A. scherman and M. arvalis was higher. If we assume that the proportion of infected faeces is not habitat-dependent and the microclimatic conditions are favourable to egg survival, then the risk of parasite transmission to intermediate hosts should be higher in these two micro-scale habitats (Guislain et al, 2007). In the Jura Mountains, E. multilocularis prevalence in rodents was very low on a regional scale (approximately 1‰) (Giraudoux et al, 2002).…”
Section: Countryside Environmentsmentioning
confidence: 99%
See 3 more Smart Citations